Chemical-Free Dyeing of Cotton With Functional Natural Dye: A Pollution-Free and Cleaner Production Approach - Rehman, Abdur; Irfan, Muhammad; Hameed, Arruje; Saif, Muhammad Jawwad; Qayyum, Muhammad Abdul; Farooq, Tahir (Frontiers in Environmental Science, 2022)
This study is a novel approach toward the development of a chemical-free and sustainable textile dyeing process with minimum environmental risks. Cotton fabrics were cationized with (3-chloro-2-hydroxypropyl) trimethylammonium chloride in four concentrations and subsequently dyed with the black tea extract. Eco-friendly colorant extraction from raw black tea leaves was carried out in aqueous media avoiding the use of hazardous organic solvents. The major coloring components in the black tea extract are polyphenols like theaflavins and thearubigin. Cationized cotton fabrics were dyed in four different shade depths without employing auxiliary chemicals in the dyeing process. For comparison, un-cationized cotton was dyed with the same extract in the same shades. It was observed that un-cationized cotton samples exhibited very low color strength (K/S) values and excellent colorfastness rating. However, the cationized samples showed remarkable enhancement in their color strength with an increase in the concentration of the cationizing agent. Furthermore, colorfastness to washing, rubbing, and perspiration was excellent, but lightfastness was poor. Deep shades (K/S = 8.996) were obtained for cotton sample cationized (20 g/l) and dyed (6%) shades. Thus, the extraction of natural colorants without toxic solvents, economically viable surface modification of cotton, and chemical-free dyeing render the dyeing process cleaner, sustainable, and practicable at an industrial scale. The textile units could easily adopt this approach to regulate a pollution-free dyeing process without modifying their existing infrastructure.